Comparison of the methods of the correction of the venous thromboembolism in bariatric surgery using the low-frequency thromboelastography: our experience - Tarabrin, O.; Sukhonos , R.; Suslov, O.; Kirpichnikova, K.; Bugaenko, E. (Journal of Education, Health and Sport, 2023)
Introduction. In the world of obesity and its complications annually dies about 2.8 million people. Obesity is an independent factor of the risk of venous thromboembolism (VTE), as it interferes with the internal and external pathways of coagulation, as well as in anticoagulant mechanisms, which leads to a hypercoagulation state. Reducing excess body weight in patients with morbid obesity by bariatric surgery is becoming increasingly popular, as barium therapy is an effective means of treating obesity and related concomitant diseases. Advantages of bariatric surgery are undeniable, as well as risks. Despite many blood coagulation studies, cases of thromboembolism in such patients are becoming more frequent, especially during surgical interventions and in the postoperative period, given that the operation is a trigger factor in the development of thromboembolism. Materials and methods. A hemostasis system was studied in 63 patients with BMI> 35 kg / m2. All patients were divided into 3 groups. 1 group (n=20) - patients who received combined therapy: Enoxaparin sodium 0.1% 0.2 ml / kg 2 times a day every 12 hours and Pentoxifylline 100 mg 2 times a day every 12 hours; The 2nd group (n= 17) - patients treated with: Enoxaparin sodium 0.1% 0.2 ml / kg 2 times daily for every 12 hours; Group 3 (control): 26 people with obesity, BMI> 35, not subject to bariatric surgery. The study of the hemostasis system was carried out using low-frequency piezoelectric thromboelastography (LPTEG) immediately after hospitalization and on 1,3,5 days after bariatry. The following blood coagulation constants were checked: Contact Coagulation Intensity; intensity of coagulation drive; maximum bunch density; Fibrinolytic activity is the index of retraction and lysis of the clot. Results. In patients of group 1 (anticoagulants + antiplatelet agents) the risk of thrombotic complications is lower, since this therapy has reduced the value at all stages of hemocoagulation to the reference values; Patients in group 2 (anticoagulants), despite the normalization of the coagulation unit, had an increase in the values of aggregation and fibrinolysis, relative to the norm, which means the risk of thrombotic complications remains high. Conclusions. The instrumental method of NPTEG allowed to adequately estimate the system of hemocoagulation in dynamics in patients with morbid obesity, with BMI ≥ 35 kg / m2; This category of patients has shown a high risk of VTE; It has been proved that for an adequate prevention of VTE in obese patients undergoing bariatric surgery, the combination of anticoagulants and antiplatelet agents is more effective than monotherapy with anticoagulants.